Analysis of the Need for Development of a Virtual Space for Student Guidance and Counseling - Wahyuni, Sri; Zamroni; Rizka Apriani; Fajarianto, Otto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
This research aims to develop an innovative virtual space for academic guidance as a means of increasing student competency. The development method involves interactive design and the integration of information technology to create an engaging and effective learning environment. In addition, this research will evaluate the impact of using this virtual space on improving students' academic skills, as well as analyzing their perceptions and experiences during the guidance process. It is hoped that the results of this research can make a significant contribution to the development of innovative academic guidance methods and support increasing student competence in this digital era.